ASPEK KEBENCIAN DAN KEHORMATAN DALAM PUISI PERANG ANTARA BELANDA DAN ACEH - Mohd Harun (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The study examines war poems between the Dutch and Aceh in the aspect of hatred and honor. The data of war poems were obtained from written sources produced by the Dutch and Aceh. The data were analyzed by using sociology of literature approach. The results of the study were (1) the Dutch’s hatred for Aceh, which was labelled as the den of criminals, traitor, and anathema, was implanted before the aggression through poems sung by the military who were sent to Aceh; (2) the Acehnese’s hatred for Kaphe Belanda (Dutch infidel), which was labelled as heretic infidel, maledict infidel, cursed infidel, and Jewish infidel, was implanted through war poems that made Acehnese willing to die in fightings against the Dutch wherever they were, either in wartime or cease period; (3) for the Dutch, fighting against Aceh was to defend the honor of the mother land and for the purpose ofobtaining a medal of honor; and (4) for Acehnese, fighting against the Dutch was acollective obligation and to die as a martyr in a holy war is the highest honor of beingan Acehnese